2016
DOI: 10.1017/s1479262116000034
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genetic diversity and structure in a genebank collection of red clover (Trifolium pratenseL.) using SSR markers

Abstract: Genetic diversity of a red clover global collection was assessed using 36 simple sequence repeat (SSR) primers representing all seven linkage groups (LGs). The number of fragments amplified ranged from 1 to 6 for all the primers. Primer RCS0060 detected highest number of fragments, whereas four SSRs viz., RCS0899, RCS1594, TPSSR40 and RCS6927 amplified single fragment. Size range of amplicons generated by all the primers varied from 100 to 400 bp. Polymorphism information content values ranged from 0.301 to 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 20 publications
2
11
0
3
Order By: Relevance
“…PIC values determined in the work of Dias et al (2008) were in the range of 0.64 to 0.85 for the three populations and in the range of 0.70-0.91 for 56 individuals of red clover. Gupta et al (2016) reported SSR PIC values range from 0.301 to 0.719 for red clover genotypes, and Vymyslicky et al (2012) found SSR PIC values to be in the range of 0.4 to 0.86.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…PIC values determined in the work of Dias et al (2008) were in the range of 0.64 to 0.85 for the three populations and in the range of 0.70-0.91 for 56 individuals of red clover. Gupta et al (2016) reported SSR PIC values range from 0.301 to 0.719 for red clover genotypes, and Vymyslicky et al (2012) found SSR PIC values to be in the range of 0.4 to 0.86.…”
Section: Discussionmentioning
confidence: 98%
“…Vymyslicky et al (2012) reported that the number of alleles per locus in red clover ranged from 3 to 8, with an average of 4.4. Gupta et al (2016) determined the lowest value of the average number of alleles per locus in the red clover, which amounted 3.18. PIC values determined in this study were somewhat lower when compared to the results of other authors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…В источниках литературы и ранее встречались сведения о невысоком уровне генетической изменчивости клевера лугового, выявленном с использованием разных типов молекулярных маркеров (Kongkiatngam et al, 1995;Kölliker et al, 2003). Однако большинство исследователей отмечают значительную вариабельность, причем более высокую внутри сортов и популяций, чем на межпопуляционном уровне (Dias et al, 2008;Gupta et al, 2016).…”
Section: результаты и обсуждениеunclassified
“…Ю. Дугарь и В. Попов с помощью SSR-маркеров выявляли ДНК-полиморфизм между сортами украинской селекции (Dugar, Popov, 2013). Исследовательские группы из Индии и Сербии на основе SSR-маркеров изучали генетическую изменчивость образцов клевера лугового из коллекций разных стран мира (Gupta et al, 2016;Radinovic et al, 2017). В России исследования по изучению ДНК-полиморфизма клевера лугового на основе SSR-маркеров для идентификации и генетической паспортизации селекционных достижений только начинают появляться (Klimenko, Kozlov, 2018; Klimenko et al, 2019).…”
Section: Introductionunclassified